2014
DOI: 10.1016/j.febslet.2014.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine is transferred from chemically‐defined liposomes to chloroplasts through proteins of the chloroplast outer envelope membrane

Abstract: Edited by Ulf-Ingo FlüggeKeywords: Phosphatidylcholine (PC) Chloroplast Liposome Lipid uptake a b s t r a c t Chloroplasts maintain their lipid balance through a tight interplay with the endoplasmic reticulum (ER). The outer envelope membrane of chloroplasts contains a large proportion of the phospholipid phosphatidylcholine (PC), which is synthesized in the ER and also a possible precursor for thylakoid galactolipids. The mechanism for PC transport from the ER to chloroplasts is not known. Using isolated chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The ER proliferation and the absence of DGTS in chloroplast purified fraction indicates that DGTS is produced in the ER and not transported into the chloroplasts. It confirms that lipid trafficking from the ER toward chloroplast membrane is selective as it was already shown that PC was able to be transferred from liposomes to chloroplast but not PE (Yin et al, 2015). The transfer of DGTS to the rest of the endomembrane system could be achieved by vesicular trafficking but this need to be investigated as well as a potential mitochondria transfer.…”
Section: Discussionsupporting
confidence: 58%
“…The ER proliferation and the absence of DGTS in chloroplast purified fraction indicates that DGTS is produced in the ER and not transported into the chloroplasts. It confirms that lipid trafficking from the ER toward chloroplast membrane is selective as it was already shown that PC was able to be transferred from liposomes to chloroplast but not PE (Yin et al, 2015). The transfer of DGTS to the rest of the endomembrane system could be achieved by vesicular trafficking but this need to be investigated as well as a potential mitochondria transfer.…”
Section: Discussionsupporting
confidence: 58%
“…Further work confirmed that ER membranes can donate labeled phospholipids to isolated chloroplasts in a time and temperature dependent fashion without any cytosolic factors (Andersson et al 2004;Xu et al 2008;Yin et al 2015). Additionally, protease digestion to remove chloroplast OEM proteins impaired PC uptake, though proteins responsible have yet to be identified (Yin et al 2015). It is also possible that soluble lipid transfer proteins are involved, as soluble proteins were previously observed to increase transfer of PC to the chloroplast (Miquel et al 1988).…”
Section: Lipid Transport To the Chloroplastmentioning
confidence: 68%
“…Subbsequent incubation of the chloroplasts with phospholipase C generated DAG from PC, which allowed synthesis of labeled MGDG (Oursel et al 1987). Further work confirmed that ER membranes can donate labeled phospholipids to isolated chloroplasts in a time and temperature dependent fashion without any cytosolic factors (Andersson et al 2004;Xu et al 2008;Yin et al 2015). Additionally, protease digestion to remove chloroplast OEM proteins impaired PC uptake, though proteins responsible have yet to be identified (Yin et al 2015).…”
Section: Lipid Transport To the Chloroplastmentioning
confidence: 82%
“…Isolated plastids are able to uptake PC, but not PE, coming from microsomes or liposomes (i.e., small vesicles mimicking membranes), supporting the transfer of PC molecules from the ER to plastids (Andersson et al, 2004; Yin et al, 2015). In addition, a lipid flippase, ALA10, able to translocate phospholipids from one leaflet of a membrane to another, was reported to stimulate PC export from the ER in Arabidopsis thaliana (Poulsen et al, 2015; Botella et al, 2016).…”
Section: Lipid Trafficking During Plant Developmentmentioning
confidence: 96%